The effect of HIV-1 regulatory proteins on cellular genes: derepression of the IL-2 promoter by Tat - Ehret, Andreas; Li-Weber, Min; Frank, Rainer; Krammer, Peter H. (European journal of immunology, 2001)
In HIV-infected individuals dysregulation of the immune system is characterized by severe disorders of the cytokine network. Increase secretion of IL-2, the major T cell growth and differentiation cytokine, may play a decisive role in sensitization of T cells for activation induced apoptosis and indirect death of activated T cells through augmented virus replication. We investigated the cause of enhanced IL-2 secretion and found that the HIV Tat induces this effect. We demonstrate that increased IL-2 secretion is due to Tat-enhanced IL-2 promoter activation. Tat derepresses and activates the distal AP-1 site (position -185 to -177) in the IL-2 promoter. In nonstimulated T cells a repressor complex containing NF-IL6, JunB, c-Fos and Fra-1 is formed on the AP-1IL-2/d site and represses IL-2 promoter activity. After T cell activation, a heterodimeric activator containing p65 and c-Jun binds to the AP-1IL-2/d site. HIV Tat enhances activation of NF-κB and consequently, activates the AP-1IL-2/d site. Our data provide evidence for a novel mechanism by which HIV Tat dysregulates IL-2 production and therefore may contribute to the HIV-1 infection in a way yet to be clarified.
Gesehen am 28.04.2020